Kinetic modelling of peat water treatment with continuous electrocoagulation using aluminium electrodes - Nazeri, Abdul Rahman; Allene Albania, Linus; Calvin, Jose Jol; Nur Syahida, Abdul Jalal; Chieng, Kwong Ming; Wan Wafi Shahanney, Wan Borhan; Nooranisha, Baharuddin; Shaleen Nur Ain, Samsul; Nurshazatul’aini, Abdul Mutalip (Elsevier Ltd., 2023)
Peat water source could be utilized to mitigate water scarcity issues that are experienced by the local communities in Sarawak rural areas. However, this water source needs to be treated prior to domestic consumption due to the levels of humic substances being incomparable to the Malaysia water quality standards. As such, this study aims to formulate the kinetic models for peat water treatment with continuous electrocoagulation system by using aluminium electrodes. Correspondingly, the kinetic models are formulated with adsorption isotherm models and variable kinetic order models (VOK). Subsequent, the study has found that the formulation of VOK model with Freundlich isotherm model is well fitted to the experimental data due to the regression coefficient (R2) values being higher than 0.90 in comparison to VOK-Langmuir and VOK-Jovanovic models. Additionally, the formulated VOK-Freundlich model able to predict the removal of turbidity, chemical oxygen demand, and colour from peat water with continuous electrocoagulation treatment system. Overall, this study demonstrates that peat water treatment with continuous electrocoagulation system by using aluminium electrodes follows VOK-Freundlich kinetic model.